Customer Satisfaction as a Mediator Between Service Quality, CRM, and Customer Loyalty - Made Dwika Dinda Damayanti; Ni Made Wahyuni; Made Setini (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2026)
Purpose – This study aims to examine the effects of service quality and customer relationship management (CRM) on customer loyalty, with customer satisfaction as a mediating variable, among Bank Permata customers in Bali. Methodology/approach – This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 115 Bank Permata customers in Bali. The analysis was conducted using Partial Least Squares (PLS) to test the direct and indirect relationships among variables. Findings – The results reveal that service quality does not have a significant direct effect on customer loyalty, but it has a positive and significant influence on customer satisfaction. CRM has a positive and significant effect on both customer satisfaction and customer loyalty. Customer satisfaction also positively and significantly affects customer loyalty. Furthermore, mediation analysis indicates that customer satisfaction fully mediates the relationship between service quality and customer loyalty, while it partially mediates the relationship between CRM and customer loyalty. Novelty/value – This study provides empirical evidence that customer satisfaction plays a crucial bridging role in strengthening loyalty within the banking sector, particularly in the context of Bank Permata Bali. The findings highlight the importance of improving service performance and implementing sustainable, personalized CRM strategies to enhance long-term customer loyalty.